2009
DOI: 10.1111/j.1939-165x.2008.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hepatic gene expression in dogs with experimentally induced nutritional iron deficiency

Abstract: Changes in hepcidin and transferrin receptor gene expression were consistent with the known biology of iron metabolism. The decrease in expression of a gene identified as "similar to calreticulin," while not statistically significant, was consistent with the findings of other investigators that suggest iron plays a role in calreticulin expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Iron deficiency was also considered to be the cause of decrease in hepatic non-heme iron content and hepcidin gene expression during the later period in this experiment. It has been reported that hepcidin gene expression markedly decreases in dogs with experimentally induced nutritional iron deficiency [14]. However, the hepatic non-heme iron content and hepcidin gene expression returned to the levels seen before turpentine injection, and the intensity of bone marrow iron staining did not decrease in the later period in this experiment.…”
Section: Discussionmentioning
confidence: 49%
“…Iron deficiency was also considered to be the cause of decrease in hepatic non-heme iron content and hepcidin gene expression during the later period in this experiment. It has been reported that hepcidin gene expression markedly decreases in dogs with experimentally induced nutritional iron deficiency [14]. However, the hepatic non-heme iron content and hepcidin gene expression returned to the levels seen before turpentine injection, and the intensity of bone marrow iron staining did not decrease in the later period in this experiment.…”
Section: Discussionmentioning
confidence: 49%
“…IL-6 was induced within three hours after injection of mice with LPS, and urinary hepcidin peaked at six hours, followed by a significant decrease in serum iron [38]. There is also clear evidence that natural and induced iron deficiency in animals or humans strongly correlates with increased tissue TfR1 expression [39][40][41][42][43][44]. Finally, published data demonstrate that iron supplementation inhibits and iron chelation enhances MACV or JUNV GP-mediated entry in two cell lines [11].…”
Section: Iron Sequestration Tfr1 Expression and Arenaviral Hemorrhamentioning
confidence: 99%
“…Hypoxia has multiple effects on the expression of a vast array of genes, but this has been almost entirely investigated in vitro [8] or in experimental animals [9]. Iron deficiency is a common nutritional disorder, and it enhances pathways that are associated with hypoxia as iron is required for optimal activity of prolyl hydroxylases (PHDs) that are principal negative regulators of hypoxia inducible factors (HIFs) [10; 11]; iron deficiency also has hypoxia-unrelated metabolism-regulating roles [12; 13; 14; 15; 16]. Investigating the relationship between gene expression and the nutritional environment is important for understanding the complications of genetic disorders and for the development of optimal personalized approaches to medical care [17].…”
Section: Introductionmentioning
confidence: 99%